Viral vs moral - Mohamad Hasnur, Abdul Hamid (2017)
As the technology evolve, the way people live their life also have changed when more time were spend in social media such as Facebook, Twittter, Instagram, Whatsapp and many more. But how far this changing in lifestyle affected the society?